2012
DOI: 10.1134/s1995078012030135
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of membrane activity of water-soluble polysubstituted fullerene derivatives by luminescence methods

Abstract: Patterns of the interaction between water soluble polysubstituted fullerene derivatives (PFDs) and the lipid bilayer of phosphatidylcholine liposomes were investigated by applying triplet and fluorescent probes. Objective quantitative criteria have been proposed for the evaluation of membranotropic action of chemical substances, notably, fullerene derivatives that quench fluorescent probes with different localizations within the membrane. Thus, the defined criteria are the rate constants for the quenching of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…It was shown that WS[60]FDs interact with hydrophilic sites of the phospholipid membranes, and the character of this interaction is dened by the charge state of WS[60]FDs. 30 Known therapeutic targets for the treatment of Alzheimer's disease are the membrane-integrated enzyme monoamine oxidase B (MAO-B), free radical oxidation, and recently, b-amyloidal brils. 31,32 It is known that MAO-B is one of the key enzymes metabolizing dopamine in the brain to a nal product, homovanillic acid.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that WS[60]FDs interact with hydrophilic sites of the phospholipid membranes, and the character of this interaction is dened by the charge state of WS[60]FDs. 30 Known therapeutic targets for the treatment of Alzheimer's disease are the membrane-integrated enzyme monoamine oxidase B (MAO-B), free radical oxidation, and recently, b-amyloidal brils. 31,32 It is known that MAO-B is one of the key enzymes metabolizing dopamine in the brain to a nal product, homovanillic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of singlet oxygen 1 O 2 formation has been performed by a standard method using 1,3-diphenylisobenzofuran (DPBF) [ 31 ]. To introduce a hydrophobic probe DPBF to an aqueous solution, it was incorporated into the phosphatidylcholine liposomes using a modified method [ 32 , 33 ]. The aqueous solution containing DPBF (0.05 mM of DPBF in liposomes, 0.5·mM of lecithin) and the photosensitizer (5 μM), in a 10 × 10 mm quartz cuvette was irradiated with the setup, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of liposomes solution. Phosphatidylcholine (lecithin) from egg yolk (Sigma) was used to prepare liposomes’ solution according to the method described in [ 32 , 33 ]; lipid concentration in the cuvette was 100 μM.…”
Section: Methodsmentioning
confidence: 99%
“…The kinetics of eosin Y phosphorescence decay was recorded using Cary Eclipse fluorescence spectrometer (Varian, Palo Alto, CA, USA). Before measurements, oxygen was deleted from the sample by adding 1 μg of glucose oxidase and 1 mg of glucose, as described previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%